A hypothermia mimetic molecule (zr17-2) reduces ganglion cell death, gliosis, and electroretinogram distortion in male rats subjected to perinatal asphyxia - Rey-Funes, Manuel; Fernández, Juan Carlos; Peláez, Rafael; Soliño, Manuel; Contartese, Daniela S.; Ciranna, Nicolás S.; Nakamura, Ronan; Sarotto, Aníbal; Dorfman, Verónica B.; Zapico, José M.; Ramos, Ana; de Pascual-Teresa, Beatriz; et al. (Frontiers in Pharmacology, 2023)
This is a provisional file, not the final typeset article Introduction: Perinatal asphyxia (PA) represents a major problem in perinatology and may cause visual losses, including blindness. We, and others, have shown that hypothermia prevents retinal symptoms associated to PA. In the present work, we evaluate whether a hypothermia mimetic small molecule, zr17-2, has similar effects in the context of PA. Methods: Four experimental groups were studied in male rats: Naturally born rats as controls (CTL), naturally born rats injected s.c. with 50 µl of 330 nmols/L zr17-2 (ZR), animals that were exposed to PA for 20 min at 37ºC (PA), and rats that were exposed to PA and injected with zr17-2 (PA-ZR). Fortyfive days after treatment, animals were subjected to electroretinography. In addition, morphological techniques (TUNEL, H&E, multiple immunofluorescence) were applied to the retinas. Results: A reduction in the amplitude of the a-and b-wave and oscillatory potentials (OP) of the electroretinogram (ERG) was detected in PA animals. Treatment with zr17-2 resulted in a significant amelioration of these parameters (p<0.01). In PA animals, a large number of apoptotic cells was found in the GCL. This number was significantly reduced by treatment with the small molecule (p<0.0001). In a similar way, the thickness of the inner retina and the intensity of GFAP immunoreactivity (gliosis) increased in PA retinas (p<0.0001). These parameters were corrected by the administration of zr17-2 (p<0.0001). Furthermore, injection of the small molecule in the absence of PA did not modify the ERG nor the morphological parameters studied, suggesting a lack of toxicity. Discussion: In conclusion, our results indicate that a single s.c. injection of zr17-2 in asphyctic neonates may provide a novel and efficacious method to prevent the visual sequelae of PA.